(3Tcd GdbWGYs
(3ChdgG (B:s
(3GdMeO ddg eHOY GdMbGFb GdNGQLI Yf GdMUQ hHYO abO cfJ YedJ ajeG eYfi ef GdReGf cJGHkG LGeYkG dVHW hYGeJi GdTcd GdeYQha HGdbWGY s
(3BNQgG (B:s
(3gPg GdbhGfjf Edi GdTcd GdbWGY aGf GdMGLI ai cd eKdK JYJHQ HYV RhGjGg Edi hGddg GYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdNGeS YTQs
(3GdcJGH CUdg aGQSi eZQHi hbO Je JQLeJgs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B66 (3ef faS GdHYKIs
(3HgG GdYOjO ef GdCTcGd GdgfOSjI hGdLOGhd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdQjGVjGJs